Magnetic resonance imaging of the rat brain after epileptic seizures--preliminary results - Kuchar, M Z; Jerábková, P; Brada, J; Kaspar, J; Skrivan, J; Betka, J; Langmeier, M (Prague medical report, 2006)
The magnetic resonance imaging (MRI) of the rat brain after the epilepsy seizures has been performed. As a first step, the model of the kainic acid (KA) induced seizures has been conducted to examine the possibilities of magnetic resonance imaging system kept in disposition. Seven Wistar albino rats, weighing about 300 g, were used in this study. We administered six of them with intraperitoneal injection of 10 mg/kg of KA. The control animal received corresponding volume of the saline. Every animal was examined under systemic anaesthesia induced by an intraperitoneal injection of thiopental sodium approximately 15 minutes before scanning. Diffusion-weighted imaging (DWI) has been used to acquire the coronary scans of the rat brain. The progress of hyper intense signal at the cerebral cortex and amygdale has been observed. Marked asymmetry of the signal intensity between hemispheres has been discovered. Subsequently the experimental model of audiogenic epilepsy will be conducted.
Keywords: potkani Wistar; Epilepsy; difuzní magnetická rezonance; Rats; kyselina kainová; mozek; epilepsie; Animals; krysa rodu Rattus; Kainic Acid; Rats, Wistar; zvířata; Brain; Diffusion Magnetic Resonance Imaging